The virulence improvement of Beauveria bassiana in infecting Cylas formicarius modulated by various chitin based compounds - triono bagus saputro; YUSMANI PRAYOGO; FARADIBA LAZUARDI ROHMAN; NUR HIDAYATUL ALAMI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Saputro TB, Prayogo Y, Rohman FL, Alami NH. 2019. The virulence improvement of Beauveria bassiana in infecting Cylas formicarius modulated by various chitin based compounds. Biodiversitas 20: 2486-2493. Sweet potato (Ipomoea batatas L.) is one of alternative carbohydrate source with an important role in food production, animal feed industries, and as raw materials for other derivatives. However, severe losses are constantly occurred in its production due to a notorious pest known as sweet potato weevil (Cylas formicarius). The chemical insecticides commonly used to treat the pest, but have not been efficient in eliminating C.formicarius. Beauveria bassiana is well known as a biological control agent, has been identified to effectively eliminate the pest. The aim of this research is to observe the optimum concentration of several chitin-based compounds in improving the virulence of B. bassiana. The research was conducted by the addition of chitin from various sources - insects, crustaceans and mollusk shells in a growth medium of B. Bassiana. Moreover, conidia produced by B.bassiana was exposed to C.formicarius to investigate the mortality rate of this insect. The results showed four different characteristics of colonies - velvety, wooly, pellicular, and farinaceous. The 1% chitin from Tellina sp, (P9), was found to be the best treatment which increased the growth of the colony diameter attaining 6.7cm in 20 days, increased the conidia viability that reaches 93.5%. In addition, the highest mortality percentage of C. formicarius was 91.67% in P9 at 6 days after infection. Overall, this research gave new potential sources of chitin that can be applied in improving the virulence of B. Bassiana in eliminating C. formicarius.